Respostas

2013-12-03T19:09:44-02:00
A = (x + 6).(x+2)
a = x² + 2x + 6x + 12
a = x² + 8x + 12
x² + 8x + 12 = 0 

Δ= b² - 4.a.c
Δ= 8² - 4.1.12
Δ= 64 - 48
Δ = 16

           - b   +- √Δ  
    x=   --------------------
             2. a

       - 8 +- √16
x = --------------------
             2.a

       - 8 +- 4
x = ------------------
           2.1
         -  8 + 4
 x¹ =  ................ =   - 4/2 = -2
              2

            - 8 - 4
   x² =  -------------  = - 12/2 = -6 
                2

x= -2 ou -6 

eu acho que é essa a resposta né k , beijo (:

1 5 1